The Politics Around ‘B-Grade’ Cinema in Bengal: Re-viewing popular Bengali film culture in the 1980s‒1990s - Nag, Anugyan; Bhattacharya, Spandan (Acta Orientalia Vilnensia, 2011)
Jawaharlal Nehru UniversityThe 1980–90s was a turbulent period for the Bengali cinema, the events being triggered by a series of industrial problems, the anxiety of a new film public and the pressing necessity for newer forms of articulation. During this time, Bengali popular cinema responded with newer genres of narratives (elaborated later) that emerged from dissimilar aesthetic positions and different social perspectives. But it is unfortunate that instead of engaging with this diverse range of film making practices, the journalistic and academic discourses on the 1980–90s Bengali cinema present only the ‘crisis-ridden’ scenarios of the Bengali film industry―suffering from multiple problems. Interestingly, this marginalized and unacknowledged cinema of the 1980–90s almost became synonymous to the concept of the ‘B-grade’ cinema, although it is not similar in formation, circulation and reception like the other established B-circuit or B-grade cinemas across the world. This paper aims to criticize this simpler ‘crisis narrative’ scenario by looking at the categories of class and audience and questioning the relevance of issues related to the popularity of these films. In brief, our article aims to problematize the notion of what is ‘B-grade’ cinema in the context of the Bengali cinema of the 1980–90s and by referring to this film culture, it tries to open up some other possibilities to which this notion can refer.